Breast Cancer Screening Practices in a Tertiary Care Center in the State of Qatar: A Cross-Sectional Survey - Parambil, Jessiya Veliyankodan (Breast Cancer (Dove Med Press), 2021)
INTRODUCTION: Breast cancer is the most common cancer in females. In Qatar, mortality related to breast cancer came in third after lung cancer and leukemia. In this study, we aim to comprehensively evaluate the rate of internal medicine residents and faculty compliance with breast cancer screening in Hamad Medical Corporation (Doha, Qatar), as well as to identify barriers and facilitators that could potentially augment changes to enhance physician-led cancer screening. METHODS: A cross-sectional web-based survey was distributed among internal medicine physicians between December 2018 and March 2019 at a tertiary medical centre. It focused on the knowledge, attitude, and practice of physicians regarding breast cancer screening guidelines and explored potential barriers and proposed solutions. Chi-square and t-test statistics were used to draw conclusions where appropriate. RESULTS: A total of 158 physicians responded to the survey, with a response rate of 61%. 75.9% were postgraduate trainees. Around three-quarters of the physicians mentioned that they would recommend breast cancer screening for their age-appropriate average-risk patients. There was a statistically significant difference between the trainees, consultants, and specialists regarding the modality of choice, where the majority of the trainees opted mammogram every 2 or 3 years while 44.4% of the consultants indicated yearly self-breast exam (p<0.001). The percentage of survey participants who rarely to never offer breast cancer screening in the outpatient settings was 37.8%. Unclear pathway (40%) and lack of time in clinic/ward rounds (26.5%) were the major reported barriers for cancer screening. CONCLUSION: In the current era of personalized medicine, physicians should be more oriented to local guidelines to provide optimal care to their patients. While the attitude towards breast cancer screening is positive, the overall compliance with the national recommendations is sub-optimal. Further initiatives and intervention programs are required to promote the breast cancer screening in Qatar.